EKSISTENSI PEREMPUAN DALAM PARADIGMA DAN PELAYANAN YESUS - Neston Sidauruk (Institut Agama Kristen Negeri Tarutung, 2019)
ABSTRACTThere is purpose of writing this article is to detect women existence in Jesus paradigm and ministry with apply qualitative research method. Existentially the Bible describe story as universal and neutral. But in Old Testament oftentimes be found that women and children as suborditation. But the Gospels describe that Jesus had respectable and reasonable relations with women. This reformation paradigm attitude saw by Jesus attitude that lay great store upon women attitude that go one better tradition or law of Jews by showing on an equal existence of human. The meaning is Jesus intend Jews paradigm changes totally and basicly.Keywords: Existence, Female, Paradigm, Ministry.